Arginase Promotes Skeletal Muscle Arteriolar Endothelial Dysfunction in Diabetic Rats - Johnson, Fruzsina K.; Johnson, Robert A.; Peyton, Kelly J.; Shebib, Ahmad R.; Durante, William (Frontiers in Immunology, 2013)
Endothelial dysfunction is a characteristic feature in diabetes that contributes to the development of vascular disease. Recently, arginase has been implicated in triggering endothelial dysfunction in diabetic patients and animals by competing with endothelial nitric oxide synthase for substrate L-arginine. While most studies have focused on the coronary circulation and large conduit blood vessels, the role of arginase in mediating diabetic endothelial dysfunction in other vascular beds has not been fully investigated. In the present study, we determined whether arginase contributes to endothelial dysfunction in skeletal muscle arterioles of diabetic rats. Diabetes was induced in male Sprague Dawley rats by streptozotocin injection. Four weeks after streptozotocin administration, blood glucose, glycated hemoglobin, and vascular arginase activity were significantly increased. In addition, a significant increase in arginase I and II mRNA expression was detected in gracilis muscle arterioles of diabetic rats compared to age-matched, vehicle control animals. To examine endothelial function, first-order gracilis muscle arterioles were isolated, cannulated in a pressure myograph system, exposed to graded levels of luminal flow, and internal vessel diameter measured. Increases in luminal flow (0-50µL/min) caused progressive vasodilation in arterioles isolated from control, normoglycemic animals. However, flow-induced vasodilation was absent in arterioles obtained from streptozotocin-treated rats. Acute in-vitro pretreatment of blood vessels with the arginase inhibitors Nω-hydroxy-nor-L-arginine or S-(2-boronoethyl)-L-cysteine restored flow-induced responses in arterioles from diabetic rats and abolished differences between diabetic and control animals. Similarly, acute in-vitro pretreatment with L-arginine returned flow-mediated vasodilation in vessels from diabetic animals to that of control rats. In contrast, D-arginine failed to restore flow-induced dilation in arterio